The Cumulative Capability Models: A Contingency Analysis - Vilkas, Mantas; Duobiene, Jurga; Rauleckas, Rimantas (International Journal of Industrial Engineering and Management, 2020)
Cumulative capability development models imply that there is a universal sequence in the development of performance capabilities. Despite the critique that such an approach does not align with contingency theory, efforts to identify which internal organizational characteristics affect the sequence of capabilities development have been limited. The study employs PLS-SEM multigroup analysis and a sample of 500 production firms to reveal whether internal organizational factors result in contrasting capability development sequences. The findings reveal that strategic priority choices result in significantly different capability development paths. The study suggests that strategic priority is an important contingency factor for explaining whether an organization will follow the sand cone sequence of capability development. Article history: Received (September 22, 2020); Revised (December 21, 2020); Accepted (December 22, 2020); Published online (December 28, 2020)